(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the initial efficacy in inflammation control, visual acuity improvement, and corticosteroid-sparing potential of Methotrexate after 6 months of treatment in a case series of patients with chronic or recurrent Vogt-Koyanagi-Harada disease. Subjects and methods: An interventional case series study was conducted on 12 eyes of 6 patients definitively diagnosed with Vogt-Koyanagi-Harada according to the Revised International Criteria, exhibiting a chronic course or corticosteroid dependence. Patients underwent interventional treatment with oral Methotrexate (15-20 mg/week) combined with a strictly monitored corticosteroid tapering schedule during the 6-month period from April 2025 to October 2025. Key outcome measures included best-corrected visual acuity converted to logMAR, inflammation severity grading according to SUN criteria, central macular thickness via optical coherence tomography, and adverse events. Results: At the 6-month follow-up endpoint, 5 out of 6 patients (83.3%) achieved complete clinical remission (defined as anterior chamber cells grade 0, clear vitreous). Regarding visual function, the mean best-corrected visual acuity (logMAR) significantly improved from 0.74 at baseline to 0.21 at month 6. Anatomically, the central macular thickness decreased from a mean of 490 μm to 272 μm. A promising initial “Corticosteroid-sparing” effect was observed, with 83.3% (5/6 patients) successfully tapering Prednisolone to a safe threshold (< 10 mg/day), among whom 50% (3/6 patients) reached a low dose of 5 mg/day without relapse. Adverse effects included mild gastrointestinal disturbances (1 case) and transient liver enzyme elevation (1 case), all were manageable. Conclusion: Through short-term follow-up of 6 months, low-dose Methotrexate demonstrated initial effectiveness in controlling inflammation and restoring retinal structure in chronic Vogt-Koyanagi-Harada patients, while facilitating safe corticosteroid tapering. Longer follow-up is needed to evaluate the sustainability of these results.